2018
DOI: 10.1155/2018/2394562
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Adherence with Occlu-Pad Therapy for Pediatric Patients with Amblyopia

Abstract: We aimed to examine visual acuity improvement effect and adherence in amblyopia training using tablet type vision training equipment (Occlu-pad). The subjects were 138 patients with amblyopia (average age of 5.5 ± 1.6 years old); their amblyopic visual acuity at the start of training was logMAR 0.15 to 1.3. Occlu-pad is a device that processes images such that amblyopic eyes can only view the image as it passes through polarized glasses; this is achieved by peeling off the polarizing film layer in the liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…According to the results of this systematic review, three main aspects should be analyzed in studies evaluating the effect of active vision therapy in amblyopia due to its importance in daily practice: visual acuity improvement, dose-response ratio, and adherence to treatment. Active visual therapy with dichoptic therapy, perceptual learning, anaglyph glasses, or some specific video games is effective in the treatment of anisometropic amblyopia to improve visual acuity [21][22][23][24][25][26][27][28] when it is compared with only glasses [24,26], patching [23,28], or placebo [21]. According to some authors, this improvement seems to be similar to patching [24,26,27], without a clear evidence confirming that vision therapy is more or less effective than patching for the treatment of anisometropic amblyopia in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the results of this systematic review, three main aspects should be analyzed in studies evaluating the effect of active vision therapy in amblyopia due to its importance in daily practice: visual acuity improvement, dose-response ratio, and adherence to treatment. Active visual therapy with dichoptic therapy, perceptual learning, anaglyph glasses, or some specific video games is effective in the treatment of anisometropic amblyopia to improve visual acuity [21][22][23][24][25][26][27][28] when it is compared with only glasses [24,26], patching [23,28], or placebo [21]. According to some authors, this improvement seems to be similar to patching [24,26,27], without a clear evidence confirming that vision therapy is more or less effective than patching for the treatment of anisometropic amblyopia in children.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Singh et al reported significant differences in their RCT, since the group that received dichoptic therapy and patching improved 2.4 lines in VA, while the patching group enhanced 1.8 lines [ 23 ]. In addition, good treatment compliance (mean of 69% or more) with visual therapy was reported by many authors [ 24 28 ], except a rate of 50% of compliance reported by Birch et al [ 21 ]. This is an important advantage compared to patching, as its compliance ranges from 44% to 57% [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there are experiences reported with the use of the forced-choice response method [ 67 ] that is mainly useful in discrimination and orientation tasks, as well as with the use of predefined interval increases not following a specific psychophysical methodology [ 15 ]. In addition, there are studies not mentioning or describing in detail this issue [ 13 ]. However, among the variety of psychophysical methodologies that are available, adaptative methods, such as the Best-PEST or QUEST, seem to be an appropriate option for sequential visual trainings in amblyopia, but this should be investigated further.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last few years, vision therapy has been suggested to be an effective option to promote visual rehabilitation and even to accelerate recovery when combined with patching [ 8 ]. New trends in computer-based active vision therapy have been developed for amblyopia treatment, such as the use of perceptual learning environments [ 9 , 10 , 11 ], dichoptic stimulation [ 12 , 13 , 14 ] and binocular training [ 15 , 16 ]. These video games use visual and perceptual tasks, such as orientation discrimination or letter recognition, among others, to cause a response in neuro-modulatory pathways and the enhancement of attentional skills, according to neurophysiological studies [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%